2014
DOI: 10.1097/jom.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Worksite Safety Climate, Smoking, and the Use of Protective Equipment by Blue-Collar Building Workers Enrolled in the MassBUILT Smoking Cessation Trial

Abstract: Objective In order to assess potential contributors to high injury rates and smoking prevalence among construction workers, we investigated the association of safety climate with personal protective equipment (PPE) use, and smoking behaviors. Methods Logistic regression models estimated risk ratios for PPE use and smoking using data from participants in MassBUILT smoking cessation intervention (n=1,725). Results Contractor safety climate was negatively associated with use of dust masks (RR=0.88,95%CI:0.83–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…Nevertheless, the proportion of workers who had access to, but did not use, fall protection has decreased in recent years, indicating a growing awareness of fall hazards and effective ways to prevent them, as well as increases in positive safety culture or leadership in construction. Previous research has shown an association between a better safety climate and the use of fall protection (Dutra et al, 2014; Kaskutas et al, 2013). Although PFAS is effective, details from the FACE reports show that PFAS did not provide adequate protection when used improperly.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the proportion of workers who had access to, but did not use, fall protection has decreased in recent years, indicating a growing awareness of fall hazards and effective ways to prevent them, as well as increases in positive safety culture or leadership in construction. Previous research has shown an association between a better safety climate and the use of fall protection (Dutra et al, 2014; Kaskutas et al, 2013). Although PFAS is effective, details from the FACE reports show that PFAS did not provide adequate protection when used improperly.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has described relationships between workplace safety climate, risk perception, and individual behaviors, including use of personal protective equipment and smoking (49, 50). Higher smoking rates and lower rates of PPE use were seen among workers who reported lower levels of belief that safety was valued in their workplace (49).…”
Section: Discussionmentioning
confidence: 99%
“…Higher smoking rates and lower rates of PPE use were seen among workers who reported lower levels of belief that safety was valued in their workplace (49). Previous studies have described links between smoking and work-related hazards, and have attempted to simultaneously address workplace safety to improve smoking cessation among construction workers (50).…”
Section: Discussionmentioning
confidence: 99%
“…Safety climate has been positively linked to safety outcomes as well as safety behaviors such as increased PPE use . Associations have been observed between higher general safety climate and increased PPE use, although few have examined HPD use specifically …”
Section: Introductionmentioning
confidence: 99%